Development of map matching algorithm for low frequency probe data - Miwa, Tomio; Kiuchi, Daisuke; Yamamoto, Toshiyuki; Morikawa, Takayuki (Transportation research. Part C, Emerging technologies, 2012)
► We develop some map matching algorithms for low frequency probe data. ► Introducing a link cost and multi candidate routes increases map matching accuracy. ► Additionally, introducing route choice concepts improves the accuracy. In order to lower the operating costs of a large scale probe vehicle system, countermeasures for decreasing operating cost of the system, such as lowering of data polling frequency and use an existing fleet management system, are necessary. Such countermeasures, however, reduce the accuracy of the traffic information that is generated from the collected probe vehicle data. In this study, the authors developed several map matching algorithms that can be applied to low frequency and little information probe vehicle data. These map matching algorithms were verified using actual probe vehicle data collected in the area around Nagoya, Japan. The results show that the data can be map matched with a high degree of accuracy by combining an appropriate link cost, generation of reasonable candidate routes, evaluation of the routes, and introducing the concept of a driver’s route choice.